Pembentukan Peraturan Presiden Sebagai Aturan Pelaksana Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 Untuk Perlindungan Anak Luar Kawin - Naini, Romlatust; Usanti, Trisadini Prasastinah; Sukardi, Sukardi (Fakultas Hukum Universitas Airlangga, 2023)
AbstractThe provisions of Article 43 paragraph (1) of the Marriage Law regarding the position of children out of wedlock have undergone changes, following the Constitutional Court Decision Number 46/PUU-VIII/2010. Due to the lack of certainty in addressing the criteria and rights of children out of wedlock in the provisions of Article 43 paragraph (1) of the Marriage Law. Meanwhile, there are no government regulations mandated in Article 43 paragraph (2) of the Marriage Law, which has an impact on the position of children out of wedlock. The aim of this research is to analyze the criteria, position and rights of children out of wedlock and the urgency of forming legislative regulations after the Constitutional Court Decision Number 46/PUU-VIII/2010. The methodology used in this research is normative legal research with a statutory approach, a conceptual approach and a legal reform approach. The results of this research indicate that there is a need for criteria related to the phrase